2018
DOI: 10.1097/md.0000000000009958
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of revascularization interventions compared with medical therapy in patients with ischemic cardiomyopathy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…If data is available, we also performed subgroup analyses based on region and gender to decrease heterogeneity. I 2 was also measured to assess heterogeneity between the included studies [ 17 ]. Although there was heterogeneity between the studies, this was negligible due to differences in context as well as the use of different source of data.…”
Section: Methodsmentioning
confidence: 99%
“…If data is available, we also performed subgroup analyses based on region and gender to decrease heterogeneity. I 2 was also measured to assess heterogeneity between the included studies [ 17 ]. Although there was heterogeneity between the studies, this was negligible due to differences in context as well as the use of different source of data.…”
Section: Methodsmentioning
confidence: 99%
“…There are several methods for treating and controlling ischemic cardiomyopathy in different health systems in the world: (A) medical therapy (MT) which uses anticoagulants, such as thrombolytic, beta blocker, calcium blocker, antiarrhythmic, nitrates, diuretics, antiplatelet, and lipid regulating drugs; (B) percutaneous coronary intervention (PCI) that includes piercing the skin to access the femoral artery by a catheter, catheter-guided balloon to narrow or block the coronary artery, inflating the balloon, and dilating coronary stenting to prevent reblockage; and (C) coronary artery bypass graft (CABG) that includes a bypass with saphenous vein or arterial graft pieces of breast through open narrowed or blocked coronary sternum in place. This is a surgical technique that involves opening the chest and the tight and closed coronary artery and is usually done using a vein or artery from other parts of the body (9-10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, surgical interventions seem to become outdated, and thus their relevance to modern medical practice must be questioned (16-17). A clinical trial study compared drug therapy with surgery in patients with ischemic heart disease and found no significant evidence on the benefit of these 2 therapies in reducing mortality and morbidity (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors that develop ischemic heart disease are unhealthy blood cholesterol levels, hypertension, smoking, diabetes mellitus, obesity, lack of physical activity, age and so on. And complications of this disease are Chest pain, left shoulder pain, shortness of breath and weakness ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%